CONSTRUCTING FOREIGN POLICY THROUGH DEMOCRATIC DISCOURSES: Insights from Indonesia and Turkiye - Robby, Hadza Min Fadhli (Ulul Albab: Jurnal Studi Islam, 2024)
This research explores how Indonesia and Türkiye construct their foreign policies. This research uses Lene Hansen’s discourse analysis model to closely observe how critical events in global politics, especially after 9/11, influence foreign policymakers throughout the world, especially foreign policymakers in Indonesia and Türkiye. Even though Indonesia and Türkiye had positioned themselves in different positions throughout the Cold War, both countries tried to form new doctrines for their foreign policies as they democratize themselves. To examine this construction, this study will focus on analyzing discourse as one of the instruments used in shaping foreign policy. Using official speeches and statements as primary sources for the discourse analysis, this research shows that one of the discourses that were frequently emphasized in Indonesian and Turkish foreign policy during the 2000s is the discourse of ‘democracy’. From the perspective of Indonesian and Turkish foreign policymakers, the discourse of ‘democracy’ has been placed as one of the core discourses in the process of foreign policy formation of both countries. This discourse has also played a crucial role in determining the regional and global politics of both countries.